2009
DOI: 10.1186/1471-2474-10-119
|View full text |Cite
|
Sign up to set email alerts
|

Retention of the posterior cruciate ligament versus the posterior stabilized design in total knee arthroplasty: a prospective randomized controlled clinical trial

Abstract: Background: Prosthetic design for the use in primary total knee arthroplasty has evolved into designs that preserve the posterior cruciate ligament (PCL) and those in which the ligament is routinely sacrificed (posterior stabilized). In patients with a functional PCL the decision which design is chosen depends largely on the favour and training of the surgeon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…2005, van den Boom et al. 2009). In the literature, there is no consensus regarding the outcome of CR compared with PS TKAs.…”
mentioning
confidence: 99%
“…2005, van den Boom et al. 2009). In the literature, there is no consensus regarding the outcome of CR compared with PS TKAs.…”
mentioning
confidence: 99%
“…Two typical types either substitute for a resected posterior cruciate ligament or allow its preservation [3,23], and the survivorship rates for the two designs are similar [13,20,23]. However, many surgeons prefer posterior stabilized knee prostheses to correct moderate to severe deformities.…”
Section: Introductionmentioning
confidence: 99%
“…TKA has presented excellent results with survival rates greater than 90% in follow-ups longer than 10 and 20 years. 28 The patient satisfaction rate after TKA is high (90%) and 93% of the patients would undergo this procedure again. 29 The QoL results demonstrated that TKA presents an excellent cost/benefit relationship and analysis on published studies shows that it is a highly effective procedure, with favorable results from surgical interventions.…”
Section: Discussionmentioning
confidence: 99%